Distribution of Locus of Adhesion and Autoaggregation and hes Gene in STEC Strains from Countries of Latin America - Velez, Maria Victoria (2020)
Shiga toxin-producing Escherichia coli (STEC) are zoonotic food pathogens associated with foodborne diarrheal illness, hemorrhagic colitis, and complications such as hemolytic uremic syndrome (HUS). The ability to adhere to epithelial cells is an important virulence trait, and pathogenicity islands (PAIs) play an important role on it. Some STEC carrying a PAI named locus of enterocyte effacement (LEE-positive) have been frequently associated to HUS; however, STEC that do not carry LEE (LEE-negative) have also been associated with this outcome. The burden of disease caused by LEE-negative STEC has increased recently in several countries like Argentina, Chile, and Paraguay. A new PAI –the Locus of Adhesion and Autoagregation (LAA)—has been associated to severe disease in humans. In this study, we aimed to analyze the distribution of LAA and its possible predictor, the gene hes, in LEE-negative STEC strains isolated from Chile and Paraguay from different sources. The presence of the different LAA modules and hes were detected by PCR. LAA was found in 41.6% and 41.0% of strains isolated from Chile and Paraguay, respectively. Strains were isolated from diverse origins and belonged to several serogroups including O91, O103, and O113. The hes gene was detected in 50% of the isolates from Paraguay and Chile. Therefore, the detection of LAA and hes in STEC could complement current genetic evaluation schemes, allowing to classify LEE negative STEC strains as LAA-positive or LAA-negative STEC strains.